2021
DOI: 10.3390/molecules26195762
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antibacterial and Antibiofilm Efficacy of Silver Nanoparticles Biosynthesized Using Punica granatum Leaves

Abstract: The current research work illustrates an economical and rapid approach towards the biogenic synthesis of silver nanoparticles using aqueous Punica granatum leaves extract (PGL-AgNPs). The optimization of major parameters involved in the biosynthesis process was done using Box-Behnken Design (BBD). The effects of different independent variables (parameters), namely concentration of AgNO3, temperature and ratio of extract to AgNO3, on response viz. particle size and polydispersity index were analyzed. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
3
6
0
Order By: Relevance
“…This peak could be due to excitation of SPR [ 31 ], which could determine the optical, physical and chemical properties of AgNPs [ 29 ]. The presence of a single SPR peak could explain the spherical shape of AgNPs [ 32 ]. The obtained results were in accordance with other studies focusing on AgNPs synthesized using L. salicaria extracts, in which the SPR band was observed at 415 nm [ 16 ] or in the 396–415 nm range [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…This peak could be due to excitation of SPR [ 31 ], which could determine the optical, physical and chemical properties of AgNPs [ 29 ]. The presence of a single SPR peak could explain the spherical shape of AgNPs [ 32 ]. The obtained results were in accordance with other studies focusing on AgNPs synthesized using L. salicaria extracts, in which the SPR band was observed at 415 nm [ 16 ] or in the 396–415 nm range [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, AgNPs were reported to be effective at lower concentrations than silver nitrate and antibiotics . In another similar study, it was reported that AgNPs synthesized from Punica granatum (pomegranate) leaves showed antibacterial activity at 0.050-0.125 mg mL-1 concentrations on E. coli, P. aeruginosa, S. aureus, B. subtilis and Proteus vulgaris bacteria (Singhal et al, 2021). AgNPs synthesized from the Zea mays L. (corn) plant were reported to exhibit antimicrobial effects on E. coli, S. aureus bacteria, and C. albicans fungus at concentrations of 0.084, 0.337, and 0.021 µg mL-1, respectively .…”
Section: Assessment Of Antimicrobial Activities Of Silver Nanoparticlesmentioning
confidence: 89%
“…For this purpose, a bacterial suspension was prepared, and AgNPs with concentrations of 0.1%, 0.3%, and 0.5% were added to the suspension. The samples were incubated at 37°C for 24 h. Then, the formation of bacterial biofilm at OD (optical density) of 570 nm was read using the microtiter plate method and Elisa reader (Singhal et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…After this incubation period, the wells of the 96‐well microplate were rinsed with saline phosphate buffer to eliminate bacteria in the planktonic phase. Wells that did not receive AgNPs served as the negative control group (Singhal et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%